2013
DOI: 10.1002/adma.201303123
|View full text |Cite
|
Sign up to set email alerts
|

MSN Anti‐Cancer Nanomedicines: Chemotherapy Enhancement, Overcoming of Drug Resistance, and Metastasis Inhibition

Abstract: In the anti-cancer war, there are three main obstacles resulting in high mortality and recurrence rate of cancers: the severe toxic side effect of anti-cancer drugs to normal tissues due to the lack of tumor-selectivity, the multi-drug resistance (MDR) to free chemotherapeutic drugs and the deadly metastases of cancer cells. The development of state-of-art nanomedicines based on mesoporous silica nanoparticles (MSNs) is expected to overcome the above three main obstacles. In the view of the fast development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
266
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 438 publications
(276 citation statements)
references
References 173 publications
0
266
0
4
Order By: Relevance
“…Compared to monotherapy, the combination therapy also exhibits encouraging results for TNBC, such as enhancing therapeutic efficacy, increasing overall survival rates, and lowering drug dose and side effects 10, 11, 12, 13, 14. For example, Feng et al15 demonstrated that photothermal‐chemotherapy can inhibit the proliferation and lung metastasis of TNBC by using cisplatin–polypeptide wrapped gold nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to monotherapy, the combination therapy also exhibits encouraging results for TNBC, such as enhancing therapeutic efficacy, increasing overall survival rates, and lowering drug dose and side effects 10, 11, 12, 13, 14. For example, Feng et al15 demonstrated that photothermal‐chemotherapy can inhibit the proliferation and lung metastasis of TNBC by using cisplatin–polypeptide wrapped gold nanorods.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, MSNs have been widely investigated to load anticancer drugs for overcoming MDR of cancer cells 130. Similar to other inorganic nanocarriers, the MSNs could efficiently incorporate drugs and effectively deliver them to tumor tissues through the EPR effect.…”
Section: Inorganic Nanocarriers Overcoming Drug Resistance For Cancermentioning
confidence: 99%
“…Then, HeLa cells were incubated with different concentrations of Dox in different formulations at 37°C for 24 or 48 h. As shown in Supplementary Figure S11, the lethality of free Dox at the microgram level was very small due to the effect of ATP-binding cassette transporters acting as drug efflux pumps from the cytoplasm. 37 On the other hand, given the specific targeting by HA and the dual-enzyme controlled drug release, the cellular uptake of Dox-FHMSNs@GNC@HA was higher than that of Dox-FHMSNs@GNC, which led to better anticancer activity.…”
Section: Controlled Drug Release Within the Cells And Selective Toxicitymentioning
confidence: 99%